HDX-MS study on garadacimab binding to activated FXII reveals potential binding interfaces through differential solvent exposure - Saw Yen Ow; Eugene A. Kapp; Vesna Tomasetig; Anton Zalewski; Jason Simmonds; Con Panousis; Michael J. Wilson; Andrew D. Nash; Matthias Pelzing (Taylor & Francis Group, 2023)
ABSTRACTHageman factor (FXII) is an essential component in the intrinsic coagulation cascade and a therapeutic target for the prophylactic treatment of hereditary angioedema (HAE). CSL312 (garadacimab) is a novel high-affinity human antibody capable of blocking activated FXII activity that is currently undergoing Phase 3 clinical trials in HAE. Structural studies using hydrogen/deuterium exchange coupled to mass spectrometry revealed evidence of interaction between the antibody and regions surrounding the S1 specificity pocket of FXII, including the 99-loop, 140-loop, 180-loop, and neighboring regions. We propose complementarity-determining regions (CDRs) in heavy-chain CDR2 and CDR3 as potential paratopes on garadacimab, and the 99-loop, 140-loop, 180-loop, and 220-loop as binding sites on the beta chain of activated FXII (β-FXIIa).